The city and the wilderness : Indo-Persian encounters in Southeast Asia - Khazeni, Arash (California world history library., 2020)
"The City and the Wilderness tells the story of a lost world of encounters. It recounts the journeys and micro-histories of Indo-Persian travelers across the Indian Ocean and their contacts with the Burmese Kingdom and its littoral during the turn of the nineteenth century. As Mughal sovereignty waned under mounting British colonial rule, Indo-Persian travelers and intermediaries linked to the East India Company explored and surveyed the Burmese Empire, inscribing it as a forest landscape and Buddhist kingdom at the crossroads of South and Southeast Asia. Revealing an archive of colonial Persian travel books and narratives in which Indo-Persian knowledge and perceptions of the wondrous edges of the Indian Ocean merged with the Orientalist pursuits of the East India Company, The City and the Wilderness uncovers the fading histories of inter-Asian crossings and exchanges at the ends of the Mughal world"--